The life and epistles of St Paul - Conybeare, William John, 1815-1857; Howson, John Saul, 1816-1885 (Grand rapids, MI Eerdmans, 1966)
Includes bibliographical references and index.
First published in 1852 in two volumes (Oxford Dictionary of the Christian Church).
Keywords: Paul the Apostle, Saint -- biography